The transformative effect of investments in territorial capital on poverty reduction: evidence from rural México - Aguilera, Pablo (2020)
Within the rural development debate, there has been increasing call for a stronger territorial focus that emphasizes the utilization and development of local resources along with the demands of community members. This study evaluates the impact of a poverty reduction program on two well-being dimensions: income and consumption in education and health. The empirical analysis uses a primary dataset of 2,234 beneficiary and non-beneficiary households residing in rural areas of Mexico. The results offer valuable insights on how poverty reduction programs can improve the well-being level in the targeted communities through capability-building interventions linked to investments in two forms of territorial capital, namely human capital and productive assets